Fiber-reinforced lightweight concrete slabs for the maintenance of the Soleri Viaduct. (15th September 2015) - Fantilli, Alessandro P.; Cavallo, Alessio D.; Pistone, Giuseppe
Highlights: Full-scale experimental tests were performed on one-way concrete slabs. The slabs were made with lightweight concrete and reinforced by plastic fibers. To prevent a brittle failure of the slabs, a minimum amount of fiber was defined. Plastic fibers can effectively substitute traditional steel reinforcing bars. Abstract: The Soleri Viaduct, one of the most important infrastructures in Northern Italy, has been used as an access road to the town of Cuneo for more than 80 years. It crosses the River Stura di Demonte and is about 750 m long. In a special maintenance project of the Viaduct, the current reinforced concrete slabs of the sidewalk zones need to be substituted by similar structures, but made with lightweight concrete and without the traditional steel reinforcing bars. A full-scale experimental program was performed on the new slabs to evaluate the effectiveness of the unconventional reinforcement, which consists of polymer fibers randomly dispersed within a cementitious matrix. As a result, an analogy can be drawn between the evaluation of the minimum amount of fibers and the computation of the minimum reinforcement ratio in concrete beams. A general approach, aimed at designing slightly reinforced concrete structures, is therefore introduced and applied for the fiber-reinforced lightweight concrete slabs investigated herein.